HERITAGE OF GEDE PANGRANGO MOUNTAIN THE POTENSIAL ECONOMICAL ASPECT IN CIPANAS CIANJUR JAWA BARAT - Rinayanti Laila Nurwulan (Fakultas Ekonomi UNIBBA, 2016)
Gede volcano is also known as Gedeh, Ageung or Agung, The Gede Pangrango complex dominates the cities of Cianjur, Sukabumi and Bogor lying below to the east, south, and NW respectively. The 15,196 ha, Mt. Gede Pangrango National Park is a popular weekend destination for the city population nearby and famous for its many scenis river, waterfalls, lakes, warm springs, as well a unique mountain fauna and flora rangingfrom rainforest, elfin woodland to subapine grassland. Geologically, Pangrango volcano was built over the NE rim of an older 3x 5 km caldera , and is now considered extinct. Younger Gede volcano has erupted many andesitic lava flow on its flank including historical ones. It has been noted that the city of Cianjur lies on the deposits originating from Gede , showing that the volcano underwent phases of massive flank failure. The biggest contributor to Cianjur’ GDP is from the agriculture sector amountes to 41,30 percent. While trade hotel, restaurant and services and tourism. Cianjur Regency’s transfortation system consists of road transport transport land transportation infrastructure supported by the network of national, provincial and regency levels. Overall, the exixting transportation infrastructure has reached almost all parts of Ciajur Regency. Most areas of Ciajur Regency are flowed by rivers. The exixtrncr of the rivers are supporting the residence needs for water supply. Aside from these rivers , the hydrological situation in Cianjur Regency is also determined by the presense of swamps, lakes, dams, reservoirs, springs and boreholes. Land transportation infrastructure supported by the network of national, provincial and regency level’s. Agrotourism is the potensial economical aspect in Cipanas Cianjur, West Java. This agrotourism has the potentials of nature, tourism, conservation and economic potential.